2019
DOI: 10.1210/jc.2018-02335
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Asfotase Alfa in Infants and Young Children With Hypophosphatasia: A Phase 2 Open-Label Study

Abstract: Context Long-term data on enzyme replacement treatment of hypophosphatasia (HPP) are limited. Objective To evaluate efficacy and safety of asfotase alfa in patients aged ≤5 years with HPP followed for up to 6 years. Design Phase 2 open-label study (July 2010 to September 2016). Setting Twenty-two sites; 12 countries. Participants Sixty-nine patients [median (range) age: 16.0 (0.02 to 72)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 23 publications
1
38
0
11
Order By: Relevance
“…Since 2015 Asfotase alfa (AA, Strensiq®, Alexion Pharmaceuticals, Inc., Boston, MA, USA), a human recombinant TNAP enzyme replacement therapy, is approved in many countries for long-term enzyme replacement therapy (ERT) in patients with pediatric-onset HPP to treat bone manifestations of the disease (13,14). Treatment with AA was associated with skeletal, respiratory and functional improvement and was considered a milestone in the management of severe forms with improved overall survival in this cohort (15)(16)(17)(18). But also young children, and adolescents affected by milder forms of HPP have been shown to bene t from AA by improving physical activity and reducing pain (19).…”
Section: Introductionmentioning
confidence: 87%
“…Since 2015 Asfotase alfa (AA, Strensiq®, Alexion Pharmaceuticals, Inc., Boston, MA, USA), a human recombinant TNAP enzyme replacement therapy, is approved in many countries for long-term enzyme replacement therapy (ERT) in patients with pediatric-onset HPP to treat bone manifestations of the disease (13,14). Treatment with AA was associated with skeletal, respiratory and functional improvement and was considered a milestone in the management of severe forms with improved overall survival in this cohort (15)(16)(17)(18). But also young children, and adolescents affected by milder forms of HPP have been shown to bene t from AA by improving physical activity and reducing pain (19).…”
Section: Introductionmentioning
confidence: 87%
“…23 A recent open-label multinational study to determine the long-term safety and efficacy of asfotase alfa showed that most patients improved radiographically and clinically in the first 6 years, while radiographic nonresponders had worse disease at baseline and greater amounts of neutralizing antibodies. 5 A multidisciplinary approach involving pediatric endocrinology, metabolic/genetics team, pulmonology, neurosurgery, pain management, and ophthalmology is warranted for the optimal care of such patients. 24…”
Section: Discussionmentioning
confidence: 99%
“…Паци ентке была назначена ферментозаместительная терапия рекомбинатным препаратом -асфотазой альфа, на фоне которой отмечено восстановление темпов линейного роста, устранение деформаций конечностей, грудной клетки, устранение вторичной миопатии, расширение двигательной активности ребенка. В настоящее время препарат для терапии перинатальной, инфантильной и детской форм гипофосфатазии зарегистрирован на территории РФ, однако опыт его применения в мире ограничен сравнительно небольшим числом пациентов и небольшим числом лет наблюдения* [25]. Препарат хорошо зарекомендовал себя с точки зрения эффективности и безопасности, однако период наблюдения за такими пациентами в мире составляет менее 10 лет, что затрудняет определение долгосрочного прогноза для таких пациентов.…”
Section: Discussionunclassified
“…Препарат хорошо зарекомендовал себя с точки зрения эффективности и безопасности, однако период наблюдения за такими пациентами в мире составляет менее 10 лет, что затрудняет определение долгосрочного прогноза для таких пациентов. В исследовании II фазы по применению асфотазы альфа продемонстрировано улучшение рентгенологического индекса, уменьшение на 46% доли детей, нуждавшихся в кислородной поддержке, увеличение роста и массы тела [25]. Как минимум одно нежелательное явление зафиксировано у каждого пациента: наиболее часто отмечали появление лихорадки.…”
Section: Discussionunclassified
See 1 more Smart Citation